HUBUNGAN ANTARA DURASI DAN POSTUR TUBUH PENGGUNAAN KOMPUTER TERHADAP KELUHAN NECK PAIN PADA TENAGA KEPENDIDIKAN FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS DIPONEGORO - Chriselyns Kinski Situmorang; Baju Widjasena; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2020)
This present, many office workers in the education department use computer as one of the main facilities supporting workers. Prolonged work processes with awkward postures adopted by workers during use can undoubtedly result in musculoskeletal muscle strain, namely neck muscles. This incident will cause neck pain complaints that occurs in the muscles, joints, nervous system, ligaments, and neck tendons. The purpose of this study was to analyze the association between the duration and posture of computer use for neck pain complaints. A quantitive methods with a cross-sectional survey was conducted on this study. In a survey, there were 47 educational staff selected through the selection of inclusion and exclusion criteria. The variable was measured with Nordic Body Map on the neck and Rapid Upper Limb Assessment questionnaire sent via googleform.The prevalence rates of neck pain was 66%, according to the stastical test results of neck pain complaints showed that there was no association between duration use (p = 0.875), and association between overall and neck posture (p = 0.003), (p = 0.038). Preventive measure at the workplace should be directed such as providing education related to safe work postures and making schedules and reminder message of stretching on computer screen.